EFEKTIFITAS INSTALASI PENGOLAHAN AIR (IPA) UNIT 2 TIRTA KENCANA PDAM KOTA SAMARINDA TERHADAP KUALITAS AIR MINUM TAHUN 2015 - Anrianisa Dan Prof. Dr. Fl. Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
The aim of this research is to know the process of the caltivation of  the clean water. The research is held in PDAM Samarinda.There are two kinds of the process namely  (Complete Treatment Process) covering physics, chemistry, bacteriology and  and the Partial Treatment Process. Whereas the the clean water cultivation consists of some buildings water catch presidementasion, pulsator, coagulation,speed blendering, flocking, filtrision reservoir (desinfectin), cleanwater pump, and lagoon. The standard of the water quality based on the regulation No. 492/MENKES/PER/IV/2010 dated on  19 April 2010 which arranges the requirements of the drinking water and the controlling as well which is based on the Indoneian National of Indonesia. Based on the SNI covering temperature, colour, taste, and the darkness. The quality of the chemistry such as  mercury, Arsen, Iron, Floride, Cadmium, clorida, Zenk, maangan, the samness level, amnia and arbondiocide Where as for the micrbiology covering bactery and virus. The standard Based on the Ministery of Helath No. 416/MENKES/PER/IX/by giving the narration that the water does not disturb the health, illness, technical disturbance and the handicap of estetics. The recommendations are that the drinking water has to be higient.